Prevalence of b-lactamase produced in Klebsiella pneumoniae and Enterobacter cloacae isolated from gingivitis in Al-Najaf Province, Iraq - ZAHRAA YOSIF MOTAWEQ (Smujo International, 2022)
Abstract. Motaweq ZY. 2022. Prevalence of b-lactamase produced in Klebsiella pneumoniae and Enterobacter cloacae isolated from gingivitis in Al-Najaf Province, Iraq. Nusantara Bioscience 14: 78-83. This study provides phenotypic and genotypic ?-lactamase formation data on 26 isolates of Klebsiella pneumoniae and Enterobacter cloacae isolated from patients with gingivitis checked at Al-Kafeel clinic and private clinic in Al-Najaf Province-Iraq during the period from September 2020 to February 2021. In this study, some were detected by traditional phenotypic methods, while others were detected by phenotypic and then genotypically by using the monoplex-PCR technique. The results revealed that out of 14 b-lactam resistance K. pneumoniae isolates, eight isolates (57.1%) gave positive results with the direct capillary tubes method, while 12 b-lactam resistance E. cloacae gave 6 (50%) positive results. This result indicated that enzymatic resistance was prevalent among isolates. Furthermore, the results showed that most isolates were ESBL producers according to initial and confirmatory methods. Molecular amplification of the b-lactamase enzyme blaSHV gene was detected in 8 (57.1%) and 5 (41.6%) for K. pneumoniae and E. cloacae, respectively. While all 100% of K. pneumoniae and E. cloacae isolates gave negative results for the blaGES gene. This study aimed to investigate the b-lactamase formation and detection of blaSHV and blaGES genes in K. pneumoniae and E. cloacae isolated from gingivitis diseases.